Enhancing Critical Thinking and Learning Achievement in Chemical Bonding Through Problem-Based Chemistry Module with Concept Mapping - Suprihati, Wahyurini; Saputro, Sulistyo; Sunarno, Widha (GoAcademica Research & Publishing, 2025)
The development of innovative problem-based teaching materials is a strategic effort to enhance students' critical thinking skills and learning achievement, particularly in understanding abstract concepts such as chemical bonding. This study aims to describe the results of the development stage, the feasibility, and the effectiveness of a problem-based chemistry module assisted by concept mapping in improving the critical thinking skills and learning achievement of high school students on the topic of chemical bonding. The study employed a Research and Development (R&D) method using the Borg and Gall model, modified into nine stages, and was tested in two private schools in Surakarta. Validation results indicated that the module was considered highly valid by experts and practitioners, with scores of 0.95 for content, 0.98 for presentation, 0.96 for language, and 0.94 for media aspects. The feasibility of the module, based on student responses, reached an average of 82.12%, and teacher responses 85.42%, both categorized as very good. The effectiveness of the module was demonstrated by the increase in pretest and posttest results, with N-gain scores of 0.37 (moderate category) for critical thinking skills and 0.69 (moderate category) for learning achievement. Therefore, the problem-based chemistry module assisted by concept mapping is considered feasible and effective for use in teaching chemical bonding at the high school level.